Development of Web-Based Learning Media Using Google Sites for Lines and Angles - Harahap, Adek Nilasari; Nurdalilah, Nurdalilah; Lubis, Susi Sulastri (Insitut Agama Islam Negeri Kerinci, 2024)
This study is motivated by the low understanding of students regarding the topics of lines and angles in mathematics, which is attributed to the lack of interactive and engaging learning media. The objective of this research is to develop a web-based learning media using Google Sites to enhance students' comprehension of these topics. The type of research conducted is Research and Development (R&D), adapted from the Borg & Gall model. The instruments used include achievement tests, interviews, and observations. The data analysis techniques employed are descriptive and inferential analysis for quantitative data and thematic analysis for qualitative data. The research results indicate that the web-based learning media developed using Google Sites is effective in improving students' understanding and motivation in learning. In conclusion, this media not only enhances learning outcomes but also increases student participation in the learning process. The implications of these findings suggest that the integration of web-based technology in mathematics education can enhance educational quality. However, the study's limitations include a restricted and specific sample, thus further research with larger and more diverse samples and application to other subjects is recommended.